2018
DOI: 10.1111/sms.13294
|View full text |Cite
|
Sign up to set email alerts
|

Accidental hypothermia in recreational activities in the mountains: A narrative review

Abstract: The popularity of recreational activities in the mountains worldwide has led to an increase in the total number of persons exposed to cold and extreme environments through recreation. There is little conclusive evidence about the risk of hypothermia for specific activities or populations, nor is it clear which activities are represented in the literature. This is a non-systematic review of accidental hypothermia in different recreational activities in the mountains, with a specific focus on outdoor or winter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 95 publications
(224 reference statements)
0
9
0
1
Order By: Relevance
“…In sport science, the measurement of core T is critical when evaluating research questions related to heat production, such as heat acclimatization and body cooling, exercise intensity, and effect of different environmental conditions on physiological state and performance. Monitoring of core T can be used to guarantee intensity and safety during intense heat exercise and heat tolerance tests, and to prevent exertional heat stroke (American College of Sports Medicine et al, 2007 ) or unexpected cooling (Procter et al, 2018 ). Indeed, a decrease in core T per se may significantly impair physiological functions even in a healthy subject and should be timely detected for proper triage (Danzl and Pozos, 1994 ; Paal et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…In sport science, the measurement of core T is critical when evaluating research questions related to heat production, such as heat acclimatization and body cooling, exercise intensity, and effect of different environmental conditions on physiological state and performance. Monitoring of core T can be used to guarantee intensity and safety during intense heat exercise and heat tolerance tests, and to prevent exertional heat stroke (American College of Sports Medicine et al, 2007 ) or unexpected cooling (Procter et al, 2018 ). Indeed, a decrease in core T per se may significantly impair physiological functions even in a healthy subject and should be timely detected for proper triage (Danzl and Pozos, 1994 ; Paal et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…This is a potentially life-threatening condition with high morbidity and mortality (Brown, Brugger, Boyd, & Paal, 2012;Haverkamp, Giesbrecht, & Tan, 2018). The incidence of accidental hypothermia in outdoor recreationists is unknown but seems to be more common in outdoor activities performed at high altitude or in remote areas (Procter, Brugger, & Burtscher, 2018). The American College of Sports Medicine and National Athletic Trainers' Association have called for raised awareness on the prevention, recognition and management of hypothermia and other cold injuries in sport (Cappaert, Stone, Castellani, Krause, Smith, & Stephens, 2008;Castellani et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…E. Procter, H. Brugger and M. Burtscher claim, on the basis of their research, that hypothermia cases are reported during climbing, trekking, hiking, skiing and snowboarding. Hypothermia occurs most frequently when climbing at high altitudes (Procter, Brugger, and Burtscher, 2018).…”
Section: Scientific Research In the Area Of Terrestrial Rescuementioning
confidence: 99%